Prognostic Value of the AST/ALT Ratio in Patients with Septic Shock: A Prospective, Multicenter, Registry-Based Observational Study - Sungwoo Choi; Sangun Nah; Gil Joon Suh; Sung-Hyuk Choi; Sung Phil Chung; Won Young Kim; Tae Ho Lim; Sangchun Choi; Tae Gun Shin; Sangsoo Han (Diagnostics)
Background/Objectives: Sepsis is a leading cause of mortality. The AST/ALT ratio may serve as a valuable marker for prediction in patients with various diseases. This study analyzed the prognostic value of this ratio in patients with sepsis. Methods: A retrospective analysis was performed on data from a prospective registry of septic shock patients, collected across multiple centers from October 2015 to December 2022. The main outcome of interest was mortality within 28 days. We evaluated the predictive accuracy of 28-day mortality for variables with the Sequential Organ Failure Assessment (SOFA) score, aspartate transaminase (AST) levels, alanine transaminase (ALT) levels, the AST/ALT ratio, and the combination of the SOFA + AST/ALT ratio using the area under the receiver operating characteristics curve (AUROC). A Kaplan–Meier curve was used to compare the 28-day mortality between the AST/ALT subgroups (≥1.84 and <1.84). Stepwise multivariable Cox proportional hazards analyses were performed to determine the association between 28-day mortality and an AST/ALT ratio ≥ 1.84. Results: The AST/ALT ratio had a significantly higher discriminatory ability for predicting 28-day mortality compared to either AST or ALT. In addition, combining the AST/ALT ratio with the SOFA score improved the predictive accuracy compared to the SOFA alone. A multivariable Cox regression analysis demonstrated that an AST/ALT ratio ≥ 1.84 was associated with a higher risk of death within 28 days. Conclusions: The AST/ALT ratio at emergency department admission in sepsis patients is associated with 28-day mortality and, when combined with the SOFA score, provides additional prognostic information with moderate accuracy.